Levantamento das plantas epifitas vasculares da mata ciliar das margens do rio vacacaí, São Gabriel, Rio Grande do Sul, Brasil - Hernandes, Guilherme Santarém (2013)
The vascular epiphytes are very common in tropical and subtropical forests, where competition for light and space is very large and does not allow their growth in soil. Epiphytes are not parasites as the main funding sources of water and nutrients from precipitation, accumulation of organic matter and mycorrhizal associations, do not seek food in the host plant, and therefore not parasitic plants. Thus their presence does not affect the plant where they are fixed. The work aimed to survey the vascular epiphytic species and their habitat, recognizing the host tree species in the region. The survey of epiphytes was held in the city of San Gabriel, western border of Rio Grande do Sul, in the riparian forest along the Rio Vacacaí in an area with a length of 1500 meters. The two banks of the river were analyzed and marked, and collected samples of all species vascular epiphytes and tree species, verifying the presence of phorophytes who submit a minimum DBH greater than or equal to 0.15 m in order to be subsequently identified. The group of vascular epiphytes is represented by four species belonging to two families. The most representative family Polypodiaceae was with three species, family Aspleniaceae showed only one species. Of these species, 53% have distribution in high trunk trees, in determining the abundance of epiphytic 47% are more extensive groups or individuals in various host tree, the preference for group loyalty 71% of epiphytes are indifferent to phorophyte chosen to Most species are characteristic holoepiphyte 95%. Three species epiphytic / rupicolous and epiphytic species / land. The low number of species is attributed to two facts: when treating an area with human intervention, because that site was observed a large quantity of pollutants, and the fact that in areas of riparian vegetation is low diversity of epiphytes, therefore somewhat similar to habitats where it is found greater diversity of these species.